(untitled) (Bodhi Path, 2019)
Buddhism in this part of our vast and diverse country is mainly known to be the Tibetan form of Buddhism, though we are aware of the fact that Buddhism originated in India as a religion which flourished in Tibet, now a part of Republic of china. One can debate as to the territory of Tibet and its annexation by china, but when ever Buddhism is discussed in these parts; one can identify its similarity with Tibet. The reason being the proximity of Kalimpong to Tibet, its age old trade route, which not only brought trade into India and Tibet but also along with it came its religion which is commonly known as the Tibetan form of Buddhism. If one wonders along Kalimpong one can see the influence of Buddhism from Monasteries, art, and culture which can be easily traced to Tibet.